Association between oral health status and functional independence measure on admission in convalescent hospitalized patients - Ryuzo Hara; Naoki Todayama; Tomohiro Tabata; Tomoko Mukai; Yukiko Hatanaka; Masataka Watanabe; Miki Kuwazawa; Shouji Hironaka; Nobuyuki Kawate; Junichi Furuya (BMC, 2024)
Abstract Background Oral health management has become increasingly important for acute inpatients. Older patients often require extended periods of medical care, and oral health management is necessary in the convalescent period following the acute period. During the convalescent period, oral health management remains unclear as convalescent hospitals have limited dental resources, and effective dental care must be provided if the objective of hospitalization is to improve life functions. This study aimed to clarify the relationship between daily functioning and oral health status at the time of admission to a convalescent hospital to aid in improving daily functioning in the convalescent period. Methods We included patients admitted to the rehabilitation department of a specific convalescent hospital from January to December 2021. A total of 375 patients were included in the study, with complete data records. At admission, we gathered information from the medical records, including the patient's age, sex, primary disease, Charlson Comorbidity Index, Mini Nutritional Assessment Short-Form (MNA-SF), Functional Oral Intake Scale (FOIS), Functional Independence Measure (FIM), number of teeth, and Oral Health Assessment Tool (OHAT). Statistical analysis was conducted using SPSS Ver. 27, with a significance level of 5%. Results The mean age of the 375 participants (189 men and 186 women) was 75.0 ± 12.1 years (range, 42-97 years), and over 80% were > 65 years. About 30% of major diseases could be attributed to strokes and fractures, followed by spinal cord and spine diseases. In non-stroke patients, multiple regression analysis using FIM motor, FIM cognitive, and FIM and OHAT total scores as objective variables showed that higher total scores of MNA-SF, FOIS, and lower modified Rankin Scale and OHAT were significantly associated with better FIMs. Lower OHAT scores were significantly associated with lower FOIS and MNA-SF scores, male sex, having fewer teeth, and poor dietary patterns. Conclusions The convalescent period is an opportune time to provide intensive dental care due to the generally stable condition and extended hospital stay. Our results suggest that oral health management, such as dysphagia rehabilitation and denture treatment, is important for maintaining and improving independence, a key objective of convalescent rehabilitation, and malnutrition improvement.